Diethyl phosphite-mediated switchable synthesis of bis(imidazoheterocycles) derived disulfanes and sulfanes using imidazoheterocycles and octasulfur - Reddy, Raju Jannapu; Shankar, Angothu; Kumar, Jangam Jagadesh; Sharadha, Nunavath; Krishna, Gamidi Rama (New Journal of Chemistry, 2022)
A practical and highly efficient oxidative dual C-H sulfenylation of imidazoheterocycles using odorless, inexpensive elemental sulfur in DMSO to synthesize sulfur-bridged imidazoheterocycles under metal-free conditions is reported. The amount of diethyl phosphite and sulfur powder most attractively permits a tunable synthesis of bis(imidazoheterocycle)disulfanes and bis(imidazoheterocycle)sulfanes in good to high yields. A comprehensive substrate scope with a broad range of functional group tolerance was realized, and the efficacy of the process was proved at gram-scale reactions. Next, the bis(imidazopyridine)disulfanes were smoothly reacted with various indoles under similar conditions to form the corresponding imidazo[1,2-a]pyridine-indole-derived thioethers in high yields. A plausible mechanism has been proposed based on the control experiments.

Solvent-driven mono- and bis-sulfenylation of (E)-beta-iodovinyl sulfones with thiols for flexible synthesis of 1,2-thiosulfonylalkenes and 1,2-dithioalkenes - Reddy, Raju Jannapu; Kumari, Arram Haritha; Sharadha, Nunavath; Krishna, Gamidi Rama (Journal of Organic Chemistry, 2022)
The nature of solvent is a key factor for stereoselective mono-and bis-thiolation of (E)-beta-iodovinyl sulfones with thiols under basic conditions. A novel and unprecedented vicinal bisthiolation of (E)-beta-iodovinyl sulfones with thiols under the influence of K2CO3/DMSO at room temperature for quick assembly of (E)-1,2-dithio-1-alkenes is presented. Solvent-induced stereoselective monosulfenylation of (E)-beta-iodovinyl sulfones with thiols has also been established for the synthesis of both (E)- and (Z)-1,2-thiosulfonylethenes in MeCN and MeOH, respectively. Moreover, K2CO3-mediated desulfonylative-sulfenylation of (Z)-1,2-thiosulfonylethenes with thiols in DMSO furnished unsymmetrical (Z)-1,2-dithio-1-alkenes for the first time. The solvent-dependent versatile reactivity of (E)-beta-iodovinyl sulfones has been successfully explored to provide a set of (E)-/(Z)-1,2-dithio-1-alkenes and (E)-/(Z)-1,2-thiosulfonyl-1-alkenes in good to high yields with excellent stereoselectivities. Notably, this operationally simple process utilizes a broad substrate scope with good functional group tolerance and compatibility. The efficacy of the process has been proven for gram-scale reactions, and plausible mechanistic models are outlined on the basis of experimental results and control experiments.

Pd(II)-catalyzed tandem cycloannulative-alkenylation of o-alkynyl-phenols/anilines with (E)-β-Iodovinyl sulfones: a direct strategy to construct 3-(Vinyl sulfonyl)benzoheterole derivatives - Reddy, Raju Jannapu; Sharadha, Nunavath; Krishna, Gamidi Rama (Journal of Organic Chemistry, 2023)
Benzoheterolesand vinyl sulfones are the most promisingpharmaceuticalrelevance motifs, yet the hybrid analogues of these scaffolds stillneed to be explored. We report herein a general and highly efficientPd(OAc)(2)-catalyzed intramolecular cyclization and vinylationof o-alkynylphenols/o-alkynylanilineswith (E)-beta-iodovinyl sulfones under mild reactionconditions. A direct C(sp(2))-C(sp(2)) cross-couplingis enabled for the diversity-oriented synthesis of vinyl sulfone-tetheredbenzofurans and indoles in good to high yields with excellent stereoselectivity.Notably, this tandem process was consistent at the gram scale, andin situ, generation of 2-(phenylethynyl)phenol has also been utilizedin a scalable synthesis. Late-stage synthetic transformations werealso further explored, including isomerization and desulfonylative-sulfenylation.Moreover, several control experiments were accomplished, and we proposeda plausible mechanism based on existing experimental results.

Visible-light-induced radical sulfonylative-cyclization cascade of 1,6-Enynol derivatives with sulfinic acids: a sustainable approach for the synthesis of 2,3-disubstituted benzoheteroles - Haritha Kumari, Arram; Jagadesh Kumar, Jangam; Sharadha, Nunavath; Rama Krishna, Gamidi; Jannapu Reddy, Raju (CHEMSUSCHEM, 2024)
Keywords: 1; 6-Enynols; Benzofurans; Benzothiophenes; indoles; Sulfones